Analysis Of Improving The Quality Of E-KTP Population Services - Puspita Ningrum, Algita; Sukmana, Hendra (Universitas Muhammadiyah Sidoarjo, 2022)
Writer 's it aims to analyze and describe the strategy for improving the quality of population services for E-KTP at the Porong District Office, Sidoarjo Regency which consists of a strategy for developing organizational work structures, strategies for developing service procedures, strategies for developing service infrastructure, strategies for developing organizational work culture, and developing entrepreneurship strategies. This research is a qualitative descriptive study using purposive sampling technique. In this study, the informants were the Camat Secretary as key informants, sub-district staff and the community as informants. Data collection techniques by observation, interviews and documentation. The data analysis technique uses four components, namely data collection, data reduction, data presentation, and conclusion drawing. Based on the research that has been done by the author, the result is that the service of employees in making E-KTP at the Porong District Office is maximized. The factors that hinder employees in improving services in making E-KTP are poor networks, long centralized data verification, facilities and infrastructure which is not enough, and employees who are still lacking. The strategy carried out by Porong District in improving services in making E-KTP is good cooperation between Porong District employees, socialization to the community for optimal service, recording of E-KTP in the village that has been provided by Porong District so that service is faster, and providing extra services to the community in a disciplined manner during working hours and adding facilities and infrastructure as well as adding an E-KTP recording device when needed. Keywords: , , .